Method for automatic antenna matching with transmitter output stage - D. A. Kovalevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
This work is devoted to the study of automatic antenna tuning units of the short-wave range. Devices of narrowband matching based on discrete sets of reactive elements are considered. A classification of the most frequently used automatic matching methods has been made. The advantages and disadvantages of each method are analyzed. Examples of using different approaches in commercially available devices are given. Particular attention  is  paid  to  the  calculation  method  of  matching,  as  the most  promising  for  use  in  modern communications. Assumptions are made about the reasons for its rare use in serial devices. Circuits have been developed to simulate the influence of parasitic parameters of the components of the matching circuit and the body of the tuning unit on the resulting standing wave ratio when using this method. Based on the simulation results,  conclusions  were  drawn  about  the  reasons  for  the  low  quality  of  the  calculation  method.  As  an alternative, a new method of automatic tuning is proposed, combining the advantages of computation and search methods,  which  is  based  on  modeling  the  search  process  using  a simulation  model.  The  conditions  for  its application in automatic antenna tuning units are determined. Acomparative analysis of the features of both the known methods of automatic tuning and the newly proposed one ismade.